Representaciones, emergencias y resistencias de la crítica cultural : mujeres intelectuales en América Latina y el Caribe - Díaz Orozco, Carmen (Colección Antologías del Pensamiento Social Latinoamericano y Caribeño. Serie Pensamientos Silenciados., 2017)
The women that we bring up in this volume -some better known than others and many marked by political persecution, exile and other experiences of repression and uprooting- display a powerful critical reflection on neuralgic problems of culture in Latin America and the Caribbean, from a lucid and manifest awareness of their own status as women in the struggle for a unique space of enunciation -and interpretation- in culture. Many of the names that we consider in this regard are neither strange nor unknown in the field of contemporary Latin American thought. Nor could we affirm that the thought of these women was 'submerged' or 'silenced', in the terms in which this category is usually assumed. However, we want to recover from them the works for which they deserved an unavoidable distinction in the field where they made their way with not a few difficulties: their most important productions.